1985
DOI: 10.1128/aac.28.1.103
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of topically applied 5-ethyl-2'-deoxyuridine and acyclovir in the treatment of cutaneous herpes simplex virus infection in guinea pigs

Abstract: Three percent 5-ethyl-2'-deoxyuridine (EdU) in an aqueous cream base was compared with 5% acyclovir (ACV) in polyethylene glycol ointment and 3% EdU in 95% dimethyl sulfoxide (DMSO) for efficacy in the topical treatment of an experimental dorsal cutaneous herpes simplex virus type 1 infection in guinea pigs. Topical ACV treatment reduced the mean lesion number by 15%, the lesion area by 32%, and the lesion virus titer by 60% when compared with measurements at contralateral sites treated with the vehicle alone.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
7
0

Year Published

1985
1985
1994
1994

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 18 publications
(20 reference statements)
0
7
0
Order By: Relevance
“…The minimal efficacy of topical ACV ointment in the present studies (19% reduction in lesion area) and in other experiments (8,22,23) parallels the disappointing results with this preparation in recurrent cutaneous human HSV infections in normal hosts (3,17,20,21,24,27). Similarly, the better results (31 to 73% reduction in lesion area) seen with topical PFA and topical ACV cream in our model system find parallels in the recent clinical reports which indicate that these formulations may be more effective than ACV ointment (6,7,15,19,(25)(26)(27).…”
mentioning
confidence: 73%
See 3 more Smart Citations
“…The minimal efficacy of topical ACV ointment in the present studies (19% reduction in lesion area) and in other experiments (8,22,23) parallels the disappointing results with this preparation in recurrent cutaneous human HSV infections in normal hosts (3,17,20,21,24,27). Similarly, the better results (31 to 73% reduction in lesion area) seen with topical PFA and topical ACV cream in our model system find parallels in the recent clinical reports which indicate that these formulations may be more effective than ACV ointment (6,7,15,19,(25)(26)(27).…”
mentioning
confidence: 73%
“…Further details of these procedures have been previously described (8,22 Drug flux was determined from a steady-state plot of drug concentration versus time. Further details of these procedures are available elsewhere (8,22,23).Lesion severity between drug and vehicle control-treated sites were compared by the Wilcoxon signed-rank test. The percent efficacies of different drug formulations were compared by the Mann-Whitney rank-sum procedure and in vitro flux values by Student's t test.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The compound is also active in rabbits with herpes keratitis (13,15), in mice with systemic herpetic infection (7,8), and in dorsally infected guinea pigs (46). Studies in humans have indicated positive effects with this drug for the treatment of ocular herpes (13,35).…”
mentioning
confidence: 99%